Meningkatkan Motivasi Belajar Sebagai Solusi Terhadap Problem Malas Kuliah - Okita Maya Asiyah; Muhammad Fahmi Jazuli (Arus Jurnal Pendidikan, 2022)
This research aims to solve the problem of lazy college among students into a problem that cannot be underestimated. Considering that students bear a heavy burden because they are responsible for advancing the Indonesian nation. Several factors cause students lazy college, unstable physical and psychological conditions and the surrounding environment. Increasing learning motivation is felt to be able to solve this problem and strategies that can be used by students in increasing learning motivation. Learning motivation is also influenced by internal and external factors. Ideals or desires, abilities, conditions, environment, the way lecturers teach can affect the increasing motivation to learn in students.